Dividend Policy In Joint Stock Companies - Z., Shomansurova (The American Journal of Management and Economics Innovations, 2021)
This article provides an in-depth analysis of the role and significance of dividend policy in the financial management system of joint-stock companies, describes the theory of calculating dividends, approaches to the formation of dividend policy and the basic principles of dividend policy.